Melestarikan Permainan Tradisional Papua (Batu Sepuluh dan Kayu Malele) Melalui Coaching Clinik di Pantai Base G Kelurahan Tanjung Ria, Kota Jayapura Utara (Indonesian Version) - Ansar CS; Dewi Nurhidayah; Ipa Sari Kardi; Muhammad Fitrah Mubarak; Irfan Deny Oktavian; Indra Yudistira; Evi Sinaga (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This Community Service activity aims to preserve traditional Papuan games, especially Batu Sembilan and Kayu Malele, through the Coaching Clinic at Base G Beach, Tanjung Ria Village, North Jayapura City. This activity involved 40 participants. In an effort to overcome the problem of decreasing interest and knowledge of traditional games, we use a coaching approach and direct demonstrations to introduce and improve participants' understanding and skills. The evaluation results showed a significant increase in participants from 12 people or 30% to 35 people or 88% in understanding and skills in playing traditional games. The implication is the revitalization of local culture and increased community participation in preserving Papuan cultural heritage through activities that educate and entertain simultaneously.